How does an emotional culture of joy cultivate team resilience? A sociocognitive perspective - Silja Hartmann; Matthias Weiss; Martin Hoegl; Abraham Carmeli (Journal of Organizational Behavior, 2021)
The complex nature of work tasks leads many organizations to organize work around teams, which must develop the capacity to cope with and adapt to a variety of adverse situations. However, our knowledge and understanding of what enables and inhibits the development of resilient teams, that is, change in teams' resilience capacity, have yet to be fully developed. Drawing on the build hypothesis of broaden-and-build theory, we explore the dynamic emotional, social, and cognitive elements that underlie change in team resilience capacity. We posit that a change in a team's emotional culture of joy predicts change in team resilience capacity through both social and cognitive mechanisms (i.e., change in mutuality and change in reflexivity). The results from a two-wave study involving 91 teams (comprising 1291 individual responses) indicate that the positive relationship between change in the emotional culture of joy and change in team resilience capacity is mediated by change in mutuality and change in reflexivity. This research advances the emerging literature on team resilience by theoretically delineating the underlying affective, social, and cognitive collective mechanisms that lead to within-team variability in team resilience capacity.
Keywords: 650; emotional culture; high-quality connections; positive organizational behavior; team reflexivity; team resilience